Emerging Potential of Exosomes in Regenerative Medicine for Temporomandibular Joint Osteoarthritis - Lee, Yeon-Hee; Park, Hee-Kyung; Auh, Q-Schick; Nah, Haram; Lee, Jae Seo; Moon, Ho-Jin; Heo, Dong Nyoung; Kim, In San; Kwon, Il Keun (MDPI, 2020)
Exosomes are nanosized vesicles (30-140 nm) of endocytic origin that play important roles in regenerative medicine. They are derived from cell membranes during endocytic internalization and stabilize in biological fluids such as blood and synovia. Temporomandibular joint osteoarthritis (TMJ OA) is a degenerative disease, which, in addition to chronic pain, is characterized by progressive cartilage breakdown, condylar bone remodeling, and synovitis. However, traditional clinical treatments have limited symptom- and structure-modifying effects to restore damaged cartilage and other TMJ tissues. This is due to the limited self-healing capacity of condylar cartilage. Recently, stem-cell-derived exosomes have been studied as an alternative therapeutic approach to tissue repair and regeneration. It is known that trophic regulation of mesenchymal stem cells (MSCs) has anti-inflammatory and immunomodulatory effects under pathological conditions, and research on MSC-derived exosomes is rapidly accumulating. MSC-derived exosomes mimic the major therapeutic effects of MSCs. They affect the activity of immune effector cells and possess multilineage differentiation potential, including chondrogenic and osteogenic differentiation. Furthermore, exosomes are capable of regenerating cartilage or osseous compartments and restoring injured tissues and can treat dysfunction and pain caused by TMJ OA. In this review, we looked at the uniqueness of TMJ, the pathogenesis of TMJ OA, and the potential role of MSC-derived exosomes for TMJ cartilage and bone regeneration.
Keywords: MESENCHYMAL STEM-CELL; EXTRACELLULAR VESICLES; ARTICULAR-CARTILAGE; CHONDROGENIC DIFFERENTIATION; INTRAARTICULAR INJECTIONS; CONDYLAR CARTILAGE; SUBCHONDRAL BONE; HYALURONIC-ACID; DISORDERS; TMJ